Minimum Wages and Wage Inequality in the OECD Countries - Dong-Hee Joe; Seongman Moon (East Asian Economic Review (EAER), 2020)
This paper investigates the impact of the effective minimum wage, defined as the log difference between the minimum and the median wages, on wage inequalities in the OECD countries. Unlike the previous studies that focus on single countries in which the minimum wage has no cross-sectional variation and rely instead on within-country variations of wage distribution across regions or socio-economic characteristics, we use a country panel that allows for both cross-sectional and time-series variations in minimum wage. We also control for more factors than in the previous studies whose absence may cause endogeneity. Our results confirm the previous findings that increases in minimum wage alleviate the wage inequality at the lower tail of the wage distribution, while having little effect at the upper tail. The estimated effect is larger for women than for men, which is consistent with the fact that the share of workers who are directly affected by the changes in minimum wage is bigger among women than men. An application of the IVs of Autor, Manning and Smith (2016) supports the robustness of our findings.
Keywords: J23; J31; J38; 330; Minimum Wage; Wage Inequality; Effective Minimum Wage; Labor Demand; Labor Supply